Dare to Dream : Life as One Direction - Direction, One (London Harper Collins publisher, 2012)
It's hard to believe how much has changed for us in just a few months. From five lads who didn't even know each other to making it to the X Factor final, heading off on our first tour, recording our first album and releasing our own music, we've written this book so you can get to know who we really are, where we come from and where we're going next. This is our story of life as One Direction so far and we're proud to share it all with you!
Including Illustrations
Keywords: Great Britain